Fortress Plant : How to survive when everything wants to eat you - Dale Walters (Oxford University Press, 2017)
The survival of plants on our planet is nothing short of miraculous. They are virtually stationary packages of food, providing sustenance for a vast array of organisms, ranging from bacteria and fungi, through to insects, and even other plants. But plants are master survivors, having coped with changing environments and evolving predators over much of the history of life on earth. They have surveillance systems and defences that would put most modern armies to shame. They need to have a formidable armoury, because their enemies have sophisticated weaponry of their own. In this often hostile world, battles are fought daily, often to the death. These battles are not trivial - they matter, because life on this fragile planet of ours depends on plants. In this book Dale Walters takes readers on a journey through these battlefields, exploring how predators try to fool plants' surveillance systems and, if they manage to do so, how they gain access to the nourishment they require. Incredibly, successful attackers can manipulate plant function in order to suppress any attempt by the plant to mount defensive action, while at the same time ensuring a steady supply of food for their own survival. Walters shows how plants respond to such attacks, the defences they use, and how the attacked plant can communicate its plight to its neighbours. These skirmishes represent the latest stage in an unending evolutionary war between plants and organisms that feed on them. These battles might be on a micro scale, but they are every bit as fierce, complicated, and fascinating as the battles between animal predators and prey.